Amaranth Seed Polyphenol, Fatty Acid and Amino Acid Profile - Ovidiu Procopet; Mircea Oroian (Applied Sciences, 2022)
In this paper, the extraction of polyphenols from amaranth seed using a Box–Benhken design using four factors—ultra-turrax speed, solid-to-liquid ratio (RSL), methanol concentration and extraction time—were studied. There were two responses studied for the model: total phenolic content (TPC) and total flavonoid content (TFC). The factors which influenced the most the extraction of the TPC and TFC were the RSL, methanol concentration and ultra-turrax speed. Twelve phenolic acids (rosmarinic acid, p-coumaric acid, chlorogenic acid, vanillic acid, caffeic acid, p-hydroxybenzoic acid, protocatechuic acid and gallic acid) and flavonoids (kaempferol, quercetin, luteolin and myricetin) were studied, and the most abundant one was kaempferol followed by myricetin. The amaranth seed is a valuable source of fatty acids, and 16.54% of the total fatty acids determined were saturated fatty acids, while 83.45% of the fatty acids were unsaturated ones. Amaranth seed is a valuable source of amino acids, with 9 essential amino acids being reported: histidine, isoleucine, leucine, lysine, methionine, phenylalanine, threonine, tryptophan and valine.